NEGATIVE REFLECTIONS OF PREPARATION PROCESS TO THE UNIVERSITY ENTRANCE EXAM ON STUDENTS' MATHEMATICS LEARNING - (:unkn) unknown (HACETTEPE UNIV, 2011)
The purpose of this study is to investigate negative effects of preparation process of the university entrance exam on students' solution processes and mistakes related to the function concept. To this end, a questionnaire related to the concept of function was administered to 229 students from first class of three different high schools. In this paper, only results of the analysis of the question required to determine the inverse of a function defined algebraically are presented. The results of this study have shown that preparation process of the entrance exam has negative influences on student learning in mathematics. Their procedures were based only on remembering a memorized algorithm or rule and thus their mistakes were mathematically very poor.
Keywords: Mathematics education; function concept; university entrance examination; private course